Leflunomide combined with low-dose prednisone inhibits proinflammatory T cells responses in myasthenia gravis patients - Huang, Xin; Ran, Hao; Li, Yingkai; Ma, Qian; Ou, Changyi; Qiu, Li; Feng, Huiyu; Liu, Weibin (Frontiers in Neurology, 2022)
We previously found that leflunomide combined with low-dose prednisone rapidly improved the clinical symptoms of myasthenia gravis (MG), but we had not investigated the mechanism of this phenomenon. This study documents the effect of leflunomide combined with low-dose prednisone on pro-inflammatory T cells in MG patients. We compared 32 treated MG patients with 18 controls. We collected peripheral blood before treatment and 4, 8, and 12 weeks after treatment. We extracted peripheral blood mononuclear cells (PBMCs) and stimulated them with phorbol 12-myristate 13-acetate (PMA) + ionomycin and quantified IFN-γ, IL-4, IL-17, and IL-9 secretion through ELISA. We quantified T helper (Th) cells Th1 (CD3+CD4+IFN-γ+), Th2 (CD3+CD4+IL-4+), Th17 (CD3+CD4+IL-17A+) and Th9 (CD3+CD4+IL-9+) among PBMCs. The treatment significantly reduced IL-17 and IL-9 secretion in peripheral blood but did not affect IFN-γ levels. Significant decreases in IL-17 and IL-9 appeared at week 12, and the trend of change was similar to that of the MG composite score. Flow cytometry indicated that leflunomide combined with low-dose prednisone significantly reduced the frequency of Th1 and Th17 cells. These findings demonstrate the potential of this treatment as an alternative immunosuppressive therapy for MG.